2017
DOI: 10.3389/fphar.2017.00905
|View full text |Cite
|
Sign up to set email alerts
|

New Insights into the Potential Roles of 3-Iodothyronamine (T1AM) and Newly Developed Thyronamine-Like TAAR1 Agonists in Neuroprotection

Abstract: 3-Iodothyronamine (T1AM) is an endogenous high-affinity ligand of the trace amine-associated receptor 1 (TAAR1), detected in mammals in many organs, including the brain. Recent evidence indicates that pharmacological TAAR1 activation may offer a novel therapeutic option for the treatment of a wide range of neuropsychiatric and metabolic disorders. To assess potential neuroprotection by TAAR1 agonists, in the present work, we initially investigated whether T1AM and its corresponding 3-methylbiaryl-methane analo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
43
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 37 publications
(54 citation statements)
references
References 92 publications
8
43
0
Order By: Relevance
“…Protein expression studies by Western blotting confirmed over-expression of sirtuin 6 (SIRT6) ( Figure 3a Figure S1). In agreement to our previous findings (13), increased level of LC3II, a marker for autophagosome formation, and decreased p62 protein level, a marker for autophagic protein degradation were also observed ( Figure 3c), thus confirming the efficacy of T1AM and thyronamine-like analogs, SG-1 and SG-2, as autophagy inducers in U87MG cells.…”
Section: Effects Of Sg-1 Sg-2 and T1am On The Expression Of Sirt6 Ansupporting
confidence: 92%
See 4 more Smart Citations
“…Protein expression studies by Western blotting confirmed over-expression of sirtuin 6 (SIRT6) ( Figure 3a Figure S1). In agreement to our previous findings (13), increased level of LC3II, a marker for autophagosome formation, and decreased p62 protein level, a marker for autophagic protein degradation were also observed ( Figure 3c), thus confirming the efficacy of T1AM and thyronamine-like analogs, SG-1 and SG-2, as autophagy inducers in U87MG cells.…”
Section: Effects Of Sg-1 Sg-2 and T1am On The Expression Of Sirt6 Ansupporting
confidence: 92%
“…As previously reported, T1AM and synthetic analogs SG-1 and SG-2 were found to produce a time-dependent recovery of autophagic activity in U87MG cells, due to the down-regulation of mTOR [13]. Recently, Lenzi et al provided compelling morphological evidence that the two major clearing pathways of eukaryotic cells (autophagy and proteasome), converge at the level of single organelles named autophagoproteasomes [15].…”
Section: Effects Of Sg-1 Sg-2 and T1am On Cell Clearing Systemsmentioning
confidence: 75%
See 3 more Smart Citations